Three new records of lichen genus Malmidea from China - WANG Lei1, WANG Xinyu2, XUE Junxia1, ZHANG Lulu1* (Guangxi Zhiwu)
The purpose of this study is to investigate the species diversity of Malmidea in China and further identify its species composition and distribution. The lichen specimens collected from Yunnan Province were classified based on the investigation of lichen resources in the field and the collection of lichen specimens, and combined with the methods of morphology, anatomy and chemistry. Three new records of Malmidea were reported from China, M. indica (D. D. Awasthi & M. R. Agarwal)Hafellner & T. Sprib, M. reunionis Kalb and M. hechicerae Kalb. In this paper, detailed descriptions, morphology and anatomical pictures of the recorded species were provided, and comparison and discussion were made with similar species. A key to all known Chinese Malmidea species was also provided. This study enriches the diversity of Malmidea in China, and has some significance for conservation and study of lichen diversity of China.